The Systems Constellation as an Instrument for Change Agents A Case Study, General Conceptual Model and Exploration of Intervention Effects - Bulling, Kai (Systemaufstellungen in Wissenschaft und Praxis,, 2018)
In his book Kai Bulling proposes the systems constellation as an instrument for change agents. An innovative general model of the systems constellation as a management intervention is constructed that presents the method as a synergetic combination of functional elements. This creates a new level of transparency that will support practitioners and managers in understanding its benefits and challenges as well as tailoring interventions to a specific case. Contents Organizational Change and Change Management: Phenomenon, Task and Approaches The Case Study: A New Quality Auditing Approach in an FMCG Company Case Study Findings Related to Change Agency, Management Tools and Methods The Systems Constellation as a Management Intervention: A General Conceptualization An Integrated Model of Partial Effects of the Systems Constellation Target Groups Researchers and students in the fields of change management and systemic management Change agents, managers and consultants The Author Dr. Kai Bulling wrote his dissertation under the supervision of Prof. Dr. Georg Müller-Christ at the chair of business studies and sustainable management at the University of Bremen, Germany. He has held a variety of roles in the FMCG industry in supply chain, quality and consumer service management as well as trade marketing.